Nexus between uncertainty, innovation, and environmental sustainability in BRICS: an analysis under the environmental Kuznets Curve (EKC) framework - Qamruzzaman, Md; Almulhim, Abdulateif A.; Aljughaiman, Abdullah A. (Frontiers in Environmental Science, 2025)
This study explores the relationship between trade, economic uncertainty, innovation, and climate change in BRICS nations using the Environmental Kuznets Curve framework. The research is driven by the global imperative to address climate change, with predictions of a 2.7°C rise in global temperatures by the century’s end, surpassing Paris Agreement targets. The study uses data from 1995 to 2023, employing unit root tests, cointegration tests (Bayer-Hanck and Maki), Augmented Autoregressive Distributed lagged and nonlinear autoregressive distributed lagged models, and the Fourier Toda-Yamamoto causality test to capture long- and short-term dynamics. The results demonstrate that technological and environmental innovations are critical in reducing carbon emissions, reinforcing the Environmental Kuznets Curve hypothesis that economic growth initially worsens but eventually mitigates environmental degradation. Conversely, economic, trade, and oil price uncertainties exacerbate environmental challenges by deterring investments in sustainable practices and clean technologies. A 10% increase in economic policy uncertainty, trade policy uncertainty, and oil price uncertainty significantly raise carbon emissions. In contrast, a 10% improvement in TI and EI reduces emissions, emphasizing the indispensable role of innovation in fostering environmental sustainability. To effectively combat climate change and align with international climate goals, BRICS nations must integrate their climate policies within the frameworks of the Paris Agreement and Sustainable Development Goals—notably SDG 7 Affordable and Clean Energy), SDG 9 (Industry, Innovation, and Infrastructure), and SDG 13 (Climate Action). Reducing policy uncertainties is crucial for mobilizing green investments, while subsidies, tax incentives, and strong regulatory frameworks should be prioritized to accelerate innovation-driven decarbonization. Furthermore, enhanced international cooperation, governance, and adaptive policy instruments will enable BRICS nations to navigate economic and environmental uncertainties, ensuring a transition to low-carbon economies and sustainable development pathways.